(untitled) (Eurasian Research Bulletin, 2023)
Independent Uzbekistan made a big leap in the development of architecture and urban planning in a short period of time. Today, the foundation of the great state architecture of the future is being laid, and the republic has great economic, scientific, technical and creative power. The new Uzbekistan has the power to build architecturally biconical buildings that will give a new image to Uzbekistan